2008
DOI: 10.1016/j.jesp.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Social power and emotional experience: Actor and partner effects within dyadic interactions

Abstract: A dyadic methodological and statistical approach to social power is used to test the notion that an individual's power and a partner's power have distinct effects on the individual's emotional experience. Two studies examined actor and partner effects of social power on emotion within dyadic interactions. Across interpersonal contexts and measures of social power, the individual's own social power, the orized to activate behavioral approach, was associated with positive emotion (an actor effect). In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 38 publications
4
68
1
Order By: Relevance
“…Low power was related to worse mood, heightened resource depletion, and more stress, replicating previous research (12,14,31). Notably, the effects of low power were, on average, about 2.5-times stronger (average Cohen's d to baseline = 0.48) than the effects of high power (average Cohen's d to baseline = 0.19).…”
Section: Ra Ngsupporting
confidence: 82%
See 1 more Smart Citation
“…Low power was related to worse mood, heightened resource depletion, and more stress, replicating previous research (12,14,31). Notably, the effects of low power were, on average, about 2.5-times stronger (average Cohen's d to baseline = 0.48) than the effects of high power (average Cohen's d to baseline = 0.19).…”
Section: Ra Ngsupporting
confidence: 82%
“…The approach-inhibition theory of power (3) posits that high power leads to more positive affect, and low power to more negative affect and stress. Evidence for these effects has been mixed (12,31) and may depend on having meaningful interpersonal manifestations of power (14), a feature of our experience-sampling methodology. For cognition, we tested whether power related to mental resource depletion.…”
Section: Significancementioning
confidence: 99%
“…In contrast, those in high power underestimated the level of negative emotions their partner felt toward them (Anderson & Berdahl, 2002). In another dyadic interaction study, Langer and Keltner (2008) found that people high in power reported more positive affect and that people in low power reported more negative affect than their partners. In general, the evidence suggests that in low power situations, people have less positive affect and more negative affect than those in high power.…”
Section: Emotion Regulationmentioning
confidence: 93%
“…Power sparks optimism and confidence ), authentic self-expression (Anderson & Berdahl 2002, Guinote et al 2002, action (Galinsky et al 2003), and disinhibited behavior (Gonzaga et al 2008) while decreasing vigilance (Willis et al 2011) and worries about threats or losses (Inesi 2010, Keltner et al 2003. Power holders and dominant people often experience positive affective states, such as happiness and interest (Anderson & Berdahl 2002, Berdahl & Martorana 2006, Langner & Keltner 2008, Schmid Mast et al 2009). However, evidence regarding the links between power and affect is mixed (Galinsky et al 2003, Smith & Bargh 2008, Weick & Guinote 2008.…”
Section: Power Triggers a Generalized Approachmentioning
confidence: 99%